Analysis of the Effect of Silica Fume as an Additive on the Workability and Compressive Strength of Porous Concrete - Yayan Tri Cahya; Fathoni Usman; Debby Sinta Devi (Borneo Engineering: Jurnal Teknik Sipil, 2026)
The use of porous concrete is a crucial strategy for mitigating surface water runoff in urban areas. However, low compressive strength often poses a major challenge in its application. This study aims to analyze the effect of adding silica fume on the mechanical and hydraulic properties of porous concrete. The research was conducted experimentally in a laboratory setting, following ACI 522R-10 standards for mix proportions and ASTM C39 for compressive strength testing. The silica fume content was varied at 0%, 3%, 5%, and 7% of the total cement weight, with a total of 24 test specimens, each a 10x20 cm cylinder. Test procedures included a slump test for workability, a permeability test, and a 28-day compressive strength test. The results showed that increasing the silica fume content significantly reduced the slump to 0 cm at a 7% increase, indicating that the mixture became stiffer. As the micro-structural density increased, the permeability coefficient decreased from 0.0288 cm/s to 0.0082 cm/s. Although drainage capacity decreased, the compressive strength of the concrete increased significantly by 69.6%, from 6.58 MPa to 11.16 MPa at the 7% content. The novelty of this study lies in identifying the optimal silica fume content to achieve a structural compressive strength above 10 MPa while preserving drainage functionality. These findings confirm that silica fume effectively enhances the mechanical performance and durability of porous concrete, making it highly suitable for use in eco-friendly infrastructure, such as parking lots and neighborhood roads, that require a balance between structural strength and water infiltration efficiency.©The author(s). Published by BEJTSThis is an open-access article distributed under the terms and conditions of the Creative Commons Attribution-ShareAlike 4.0 International License (CC BY-SA 4.0).Introduction: Pervious concrete is a construction material designed with a high level of porosity, allowing water to flow through its internal cavities. This material is widely used in parking areas, pedestrian paths, and sustainable drainage systems due to its ability to reduce surface runoff and increase groundwater